PENGARUH DESAIN METODOLOGI PSIKOLOGI PEMBELAJARAN PAI BERBASIS GAYA BELAJAR VISUAL TERHADAP PRESTASI BELAJAR MAHASISWA - Ainal Mardhiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
The more appropriate learning design with student learning style, the more student achievement. This study aims to describe the influence of learning design based on visual learning style on student achievement that has visual, auditorial and kinesthetic learning style. Qualitative descriptive research method with experimental form. Result of data analysis show that: 1. That student of PAI learning psychology have 3 learning style, that is visual learning style, auditorial learning style and kinesthetic learning style. 2. Student achievement that has a visual learning style that is from the average value of 58.4 to 90.7. Children who have an auditorial learning style from the average score of 52.6 to 56.6. And the kinesthetic child from an average score of 56.5 to 60. This suggests that learning design based on visual learning style can only improve student's learning achievement that has visual learning style.